The Understanding of Electrical and Computer Engineering Students to Translate Sharia Economic Texts Via Google Translate - Agus Adria (Nomico, 2024)
The potential of Islamic economics to develop in Aceh where Islamic culture and values ​​are very large and strong. Therefore, even though electrical and computer engineering students do not specifically study Islamic economics courses but live in Aceh, it is important to know the insight into Islamic economic texts. Google translate is very helpful in translating texts with nuances of sharia economics in Aceh to electrical and computer engineering students. This research was a descriptive-qualitative. The data used as a test comes from the abstract of an article by Ode and Hamizar (2024) entitled "Quantitative Analysis of the Relationship between Income and Welfare of Tuna Fishermen from the Perspective of Sharia Finance" which title is themed on sharia finance which is needed to determine the abilities of electrical and computer engineering students so that they can have insight related to the sharia economic system where this system is implemented in Aceh where they live. It can be concluded that electrical and computer engineering students can understand the interlingual translation of abstracts related to Islamic economics in English into Indonesian via Google Translate.